Social Media Marketing: Strategies and Impact on Business - Ballabh , Samita (Gyan Management Journal, 2023)
This paper aims to explore the field of social media marketing for businesses.  Individuals use social media to stay in contact with friends, family and  communities at large. Businesses of all kinds and sizes use social media to  interact with customers and promote their brand at a relatively low cost.  In today’s digital era, social media platforms have revolutionized the way  businesses engage with their target audience, build brand awareness and  promote their products and services. The study delves into various strategies used in social media marketing  such as selecting the right platform, creating compelling content,  leveraging influencer collaborations and enhancing customer engagement.  Additionally, the paper attempts to compare the effectiveness and impact  of social media marketing with traditional marketing methods. For  this purpose, a descriptive research approach was employed, utilizing  secondary data. The research findings provide valuable insights into the significance of social  media marketing as a powerful tool for businesses, especially micro and  small enterprises to reach and engage with their customers. By embracing  the power of social media marketing, businesses can effectively reach their  target audience and stay competitive in this digital age.
Keywords: Social media; Social media marketing; Businesses; engage; Brand; Social media platforms